Computer Tools in Construction - Ikmal Hisyam Bin Mubarak, Ikmal Hisyam (Universiti Teknologi Petronas, 2008)
Computer Tools have been widely used in various civil engineering applications such as for project planning, design and maintenance activities. They have been proven to be able to help engineers in performing tedious or complicated calculations or smoothen their routine work. Thereby saving the time and cost. However it observed that in construction site computer tools are not being used widely as in other civil engineering activities such as design. The main objective of this study is to investigate the awareness of the availability of computer tools in constructions field, level of usage of computer tools in constructions field and the perception of computer tools in helping the works on site in Malaysia's constructions industry. The scope of this project is focusing on the contractor, developer and professionals that involve in the constructions industry in Malaysia. This research requires the survey method involving preparation and sending questionnaires, conducting interviews and analysing the collected data which will already done within the time frame. Pilot Survey has been conducted and analyzed. At this stage, all 12 interviews have been conducted and the questionnaire distributed has been collected. The data have been being summarized in a simple format and analysed using statistical tool. The result from the analysis shows that all the respondents aware of the availability of the Computer Tools. More than fifty percent from the respondents use Computer Tools in completing their projects in 3 years which shows good indication of the level of usage of Computer Tools. The respondents also shows that simplify complicated task is the most popular perception for the advantages of Computer Tools and the most popular perception of problems chosen by the respondents are expensive and insufficient personnel concerning knowledge of Computer Tools in industry.